(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Banks serve as engines that guide the money market, financial sector, and economic growth processes. The Indian banking sector has grown at a rapid rate, particularly as we approach the fourth industrial revolution. This, however, has not been without its share of difficulties. Frauds in Indian banks have been on the rise in tandem with the rapidly increasing banking business, and there is an urgent need to restructure the banking sector in India, considering recent scams involving billions of rupees. The purpose of this study is to assess and analyse the current trend of banking frauds and their role in the on-going rise of non-performing assets in India. The study also aims to shed insight on the impact of escalating bank frauds on the banking sector's profitability in India. The report states that the number of frauds affecting the Indian banking sector has been steadily increasing in recent years, resulting to an increase in nonperforming assets (NPAs) and negatively harming the banking sector's profitability. The only way to restore the trust of Indian banks and give the banking sector a facelift is for authorities to take tough action and find new ways to prevent and reduce fraud.